(untitled) - Poénaru, Valentin (Comptes Rendus. Physique, 2025)
In the 1970s Gérard Toulouse and myself we wrote three papers on how the homotopy groups of the manifold of internal states influenced the defects of ordered media. Specifically, we showed how the algebra of homotopy groups acted on the dynamics of defects.